Precautionary Liquidity Shocks, Excess Reserves and Business Cycles - George J. Bratsiotis; Konstantinos Theodoridis (ZBW - Leibniz Information Centre for Economics, 2021)
This paper identifies a precautionary banking liquidity shock via a set of sign, zero and forecast variance restrictions imposed. The shock proxies the banking sector's reluctance to lend to the real economy induced by an exogenous preference change for liquid assets. Through the lens of a DSGE model, the precautionary liquidity shock is shown to work through two channels: reserves (balance sheet) and the deposit rate (intertemporal effect). The overall effect is a downward co-movement in output, consumption, investment, and prices, which is amplified the higher are the long-run risks in the economy and banks' responsiveness to potential risk.
Keywords: C10; C32; E30; E43; E51; G21; 330; SVAR; Sign and Zero Restrictions; DSGE; Precautionary Liquidity Shock; Excess Reserves; Deposit Rate; Risk; Financial Intermediation